KONFLIK DAN SISTEM NILAI DALAM PROSES PENYUSUNAN KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DI PEMERINTAHAN DAERAH PROVINSI BANTEN - Delly Maulana (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2020)
To realize a transparent, accountable, just, disciplined, effective, efficient, and principle-obeying the Regional Government Budget (Anggaran Pendapatan and Belanja Daerah (APBD) policy, there needs to be the involvement of al the actors, both formal (executive and legislative) and informal actors (civil societies, community groups, and interest groups) in the formulation process. Therefore, the regional government must utilize information from the people in formulating the Regional Government Budget as part of the decision-making process. This concept is an innovative policy-making process where the people are directly involved in the policy decision-making process. In this process, the open forum held every year creates an equal opportunity for the people to contribute suggestions for development priorities and the people could also monitor the implementation of government policies, especially the implementation of policies at the regional government level.In the Banten Province Regional Government context, the budgeting process is procedurally run as expected. However, substantively, the policy-formulation practices in the Regional Government Budget formulation do not yet reflect the ideal process. For example, the execution of the Deliberation of Development Planning (Musyawarah Perencanaan Pembangunan (Musrenbang)) as one of the procedures in the Regional Government Budget formulation process is substantively a formality only, and there are many public issues that should be public issues that are not recommended in the government policy agenda. Therefore, this study would like to analyze the interaction between actors and value systems in the Regional Government Budget formulation process in the Banten Province Regional Government. The method employed in this study is the quantitative study method by mapping the actors and observing the interaction phenomena actor and observing the value systems fought for in the Regional Government Budget formulation process.